2013
DOI: 10.3791/50193
|View full text |Cite
|
Sign up to set email alerts
|

Using Quantitative Real-time PCR to Determine Donor Cell Engraftment in a Competitive Murine Bone Marrow Transplantation Model

Abstract: SHORT ABSTRACT Determining donor cell engraftment presents a challenge in mouse bone marrow transplant models that lack well-defined phenotypical markers. We described a methodology to quantify male donor cell engraftment in female transplant recipient mice. This method can be used in all mouse strains for the study of HSC functions. LONG ABSTRACT Murine bone marrow transplantation models provide an important tool in measuring hematopoietic stem cell (HSC) functions and determining genes/molecules that regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…Expression of Y-linked zinc finger protein-1 (Zfy-1) along with Bcl-2 gene as internal control was quantified using qPCR analysis in the regenerated wound tissue of female mice as described earlier [16]. Standard curve was plotted using 2-δCt reading from known male/female DNA standard mixtures [21]. Cell engraftment was represented as % male DNA plotted on y-axis (mean of 2-δCt value of triplicates to the known % male DNA in the mixture with linear regression fitting).…”
Section: Genomic Polymerase Chain Reactionmentioning
confidence: 99%
“…Expression of Y-linked zinc finger protein-1 (Zfy-1) along with Bcl-2 gene as internal control was quantified using qPCR analysis in the regenerated wound tissue of female mice as described earlier [16]. Standard curve was plotted using 2-δCt reading from known male/female DNA standard mixtures [21]. Cell engraftment was represented as % male DNA plotted on y-axis (mean of 2-δCt value of triplicates to the known % male DNA in the mixture with linear regression fitting).…”
Section: Genomic Polymerase Chain Reactionmentioning
confidence: 99%
“…At 3 months post transplantation, the secondary transplant mice receiving Pim TKO cells had significantly reduced peripheral white blood cell counts (Figure 4A). Donor cell engraftment in BM was quantified at 4 months post transplantation using a quantitative PCR-based method measuring the sex-determining region Y (Zfy1) [13,16]. We found that the male donor cells engraftment in secondary Pim TKO transplant recipients was significantly lower than that in controls (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of serial transplant experiments, this finding may lead investigators to assume that HSC population is unaltered in Pim-deficient mice. The PCR-based method that we reported recently [13] allows us to reliably determine donor cell engraftment in our transplant experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were vortexed, then centrifuged to separate powdered mineral, and aspirate was processed in spin columns to isolate DNA according to Qiagen’s instructions. Quantitative PCR for both the GFP transgene and male Y chromosome-specific Zfy1 [40] was then carried out in triplicate with the QuantiTect SYBR-Green PCR kit (Qiagen, Valencia, CA) and normalized to ApoB . Murine-specific primers are specified in Table 1.…”
Section: Methodsmentioning
confidence: 99%